Abnormal partitioning of hexokinase 1 suggests disruption of a glutamate transport protein complex in schizophrenia - Shan, Dan; Mount, Daniel; Moore, Stephen; Haroutunian, Vahram; Meador-Woodruff, James H.; McCullumsmith, Robert E. (Schizophrenia research, 2014)
Excitatory amino acid transporter 2 (EAAT2) belongs to a family of Na+ dependent glutamate transporters that maintain a low synaptic concentration of glutamate by removing glutamate from the synaptic cleft into astroglia and neurons. EAAT2 activity depends on Na+ and K+ gradients generated by Na+/K+ ATPase and ATP. Hexokinase 1 (HK1), an initial enzyme of glycolysis, binds to mitochondrial outer membrane where it couples cytosolic glycolysis to mitochondrial oxidative phosphorylation, producing ATP utilized by the EAAT2/Na+/K+ ATPase protein complex to facilitate glutamate reuptake. In this study, we hypothesized that the protein complex formed by EAAT2, Na+/K+ ATPase and mitochondrial proteins in human postmortem prefrontal cortex may be disrupted, leading to abnormal glutamate transmission in schizophrenia. We first determined that EAAT2, Na+/K+ ATPase, HK1 and aconitase were found in both EAAT2 and Na+/K+ ATPase interactomes by immunoisolation and mass spectrometry in human postmortem prefrontal cortex. Next, we measured levels of glutamate transport complex proteins in subcellular fractions in the dorsolateral prefrontal cortex and found increases in the EAAT2B isoform of EAAT2 in a fraction containing extrasynaptic membranes and increased aconitase 1 in a mitochondrial fraction. Finally, an increased ratio of HK1 protein in the extrasynaptic membrane/mitochondrial fraction was found in subjects with schizophrenia, suggesting that HK1 protein is abnormally partitioned in this illness. Our findings indicate that the integrity of the glutamate transport protein complex may be disrupted, leading to decreased perisynaptic buffering and reuptake of glutamate, as well as impaired energy metabolism in schizophrenia.